Variation of chemical properties, crystalline structure and calorific values of native Malaysian bamboo species - Osman, Syaiful; Ahmad, Mansur; Zakaria, Mohd Nazarudin; A. Bakar, Balkis Fatomer; Abu, Falah; Kamarudin, Siti Hasnah; Bahari, Shahril Anuar (Society of Wood Science and Technology, 2022)
The chemical properties of four common Malaysian bamboo species locally known as Beting (Gigantochloa levis), Semantan (Gigantochloa scortechinii), Lemang (Schizostachyum brachyladum), and Akar (Bambusa vulgaris) were studied. Chemical analysis shows that the alkaline-extractive content of the Malaysian bamboo species ranged from 24.4% to 25.6%, ethanol–toluene extractive content for Malaysian bamboo species ranged from 4.0% to 7.2% and water extractive content ranged from 10.4% to 12.8%. The average value of holocellulose content for Malaysian bamboo was 64.5-70.7%, Klason lignin within 25.3- 28.4%, cellulose content was between 28.5% and 33.8%, and a-cellulose content for all bamboo species was within the range of 40.7-47.9%. The crystallinity of bamboo samples was between 42.0% and 44.4%, indicating a semicrystalline structure. Heating value of bamboo ranged between 17.0 MJ/kg and 18.1 MJ/kg with G. scortechinii having the highest heating value. The Inductive Couple Plasma Atomic Emis- sion Spectroscopy (ICP-ES) analysis showed that Potassium (K) and Calcium (Ca) were the major ele- ments in the ash of all bamboo samples. This study demonstrates the potential of native bamboo species as an alternative sustainable raw material to wood for a wide range of applications.